2018
DOI: 10.1177/1055665618776428
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Profile and Dental Caries in Cleft Lip and Palate Babies Between 0 and 3 Years Old

Abstract: The results show that the CP±L babies must be considered as a group with an increased caries risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…In a previous study by Paul and Brandt (1998) reported that the anterior segment of the maxillary arch had greater biofilm formation than the posterior region due to the surgical procedures done for lip and palate reconstruction. Another study showed that the primary lip repair surgery decreases lip elasticity and salivary flow rate, which may lead to excessive biofilm formation in the anterior region of the mouth (Durhan et al, 2019). A similar finding was shown in our study, with statistically significant reduced (low) resting (unstimulated) salivary flow rates in the upper lips of children with CL/P (35% of cases) as compared to those in the non-CL/P control group (0% of cases).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study by Paul and Brandt (1998) reported that the anterior segment of the maxillary arch had greater biofilm formation than the posterior region due to the surgical procedures done for lip and palate reconstruction. Another study showed that the primary lip repair surgery decreases lip elasticity and salivary flow rate, which may lead to excessive biofilm formation in the anterior region of the mouth (Durhan et al, 2019). A similar finding was shown in our study, with statistically significant reduced (low) resting (unstimulated) salivary flow rates in the upper lips of children with CL/P (35% of cases) as compared to those in the non-CL/P control group (0% of cases).…”
Section: Discussionmentioning
confidence: 99%
“…These factors along with reduced salivary flow and BC contribute to the creation of a favorable environment for the development of dental decay (Hicks et al, 2003; Ahluwalia et al, 2004). Until now, only a few studies have been conducted to assess the cariogenic risk factors in children with cleft lip and/ or palate (Sundell et al, 2015; Veiga et al, 2017; Sundell et al, 2018; Durhan et al, 2019; Sanghvi et al, 2019; Fowler et al, 2020). Based on these observations, this research was designed to analyze the caries protective factors, salivary parameters, and microbial counts in high caries risk children with CL/P.…”
Section: Introductionmentioning
confidence: 99%
“…The mutans streptococci constitute a group of oral cariogenic species, with S. mutans and S. sobrinus being the most frequently detected strains from the oral cavity of individuals at high risk for dental caries [44][45][46] . S. mutans has been detected from ~80% to 90% of adults' and ~50% to 100% of preschool children's oral cavity 27 , but much less frequent (~10%) in the oral cavity of infants 47,48 . The oral colonization by S. mutans is considered to take place around 26 months 49 .…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the anatomical conditions of the oral cavity of patients with CLP contribute to the high incidence of Candida species, especially C. albicans, with patterns of oral colonization by multiple species of the genus (heterogeneous colonization or multicolonization), or by a single species (homogeneous colonization or monocolonization) in greater or lesser frequency dependent on age groups and types of orofacial clefts. In part, these variations in oral Candida colonization profiles in patients with CLP could be explained by the sampling number and other factors such as decreased salivary flow, reduced defense, increased formation of dental plaque [27], reduced oral colonization by Candida due to surgical corrections [12], and patients bearing orthodontic acrylic plates [13]. Compared to children with CLP (7.2 ± 3.2 years of age) previously to surgical rehabilitation procedures, the frequencies of oral colonization by Candida species were related significantly higher for the group of infants (11.2 ± 6.6 months of age) with CLP (28.3%) and male gender (30.4%), but regardless of the surgical clinical histories [12].…”
Section: Virulence Characteristics In Vitromentioning
confidence: 99%
“…Heterozygotes represented by12,13,14,15,16,17,18,23,24,25,26,27,28,29,34,35,36,37,38,39, 45, 46, 47, 48, 49, 56, 58, 59, 68, 69, 78, 79, 4 10, 8 10, 8 11 and 9 11; -, null allele; TS, Candida albicans type strain ATCC® 10,231. M and F correspond to male and female, respectively.…”
mentioning
confidence: 99%